2022
DOI: 10.1063/5.0094820
|View full text |Cite|
|
Sign up to set email alerts
|

Aerodynamic characteristics of flexible flapping wings depending on aspect ratio and slack angle

Abstract: Experimental investigations are made for the combined effects of aspect ratio (AR), slack (βS) and pitch angles on the aerodynamic characteristics of flexible flapping wings in hover. βS is introduced as a way to indirectly alter the flexibility of the wing. An optimum AR range of 3 to 5 based on the lift coefficient is observed depending on the flexibility. For a constant AR, the intensity of the leading-edge vortex (LEV) with corresponding circulatory-based lift mitigates as βS increases beyond 2.5{degree si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 79 publications
0
1
0
Order By: Relevance
“…The wings were designed to have the same area of 0.0133 m 2 (AR = 3.01). However, there was a slight increase in r2 from 0.601 to 0.612 for y * = 0-0.15, respectively, as presented in our previous work [26]. This was less than 3.7% increase in the square of r2 , which can be critical for the aerodynamic force normalization.…”
Section: Experimental Setup and Proceduressupporting
confidence: 63%
See 3 more Smart Citations
“…The wings were designed to have the same area of 0.0133 m 2 (AR = 3.01). However, there was a slight increase in r2 from 0.601 to 0.612 for y * = 0-0.15, respectively, as presented in our previous work [26]. This was less than 3.7% increase in the square of r2 , which can be critical for the aerodynamic force normalization.…”
Section: Experimental Setup and Proceduressupporting
confidence: 63%
“…The three-ton towing tank experimental measurement facility in the KAIST SSHS laboratory was used to conduct the experiment. The facility comprises of two distinct setups for direct force/moment measurement as shown in figure 1(a) and flow visualization measurement, which are both found in our previous works [16][17][18]. The two-degree-of-freedom (2-DoF) scaled-up robotic model mainly comprised 2 servomotors (XH-430-210W, Robotis) and a gearbox.…”
Section: Experimental Setup and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors [9][10][11] showed how the aerodynamic coefficients (including the slope of the lift coefficient) of flexible micro air vehicle (MAV) wings of low aspect ratio at low Reynolds number can either grow or decrease depending on the geometry of the wing and the settings of flexible parts. Furthermore, the aerodynamic performance of flexible wings under flapping conditions (typical of bio-inspired UAVs) and the influence of their aspect ratio have also attracted attention lately [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%